Extreme value stochastic models - Aksomaitis, Algimantas (Nonlinear Analysis: Modelling and Control, 1998)
The investigation of extreme values (maxima and minima) and their asymptotics is presented. Attention is paid to the classical theory (independent observations of identical distributions). The generalizations and applications of the theory are discussed and problems are revealed.